THE FATHER OF JADIDISM AND PIONEER OF ENLIGHTENMENT IN CENTRAL ASIA (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article highlights the life and creative activity of MahmudhojaBehbudi, who is recognized as the "Father of Jadidism."Behbudi, a key figure in the Jadid movement, played a significant role in promoting education and cultural progress in Uzbekistan. The article explores his family life, contributions to the Jadid movement, his travels abroad, and the creation of various educational textbooks. Additionally, it examines his call for enlightenment and freedom through articles published in the "Samarkand" newspaper and the "Oyina" magazine.